Asymmetric Collusion and Merger Policy - Ganslandt, Mattias (2018)
In their merger control, EU and the US have considered symmetric size distribution (cost structure) of rms to be a factor potentially leading to collusion. We show that forbidding mergers leading to symmetric market structures can induce mergers leading to asymmetric market structures with higher risk of collusion, when rms face indivisible costs of collusion. In particular, we show that if the rule determining the collusive outcome has the property that the large (eficient) rm bene ts su¢ ciently more from collusion when industry asymmetries increase, collusion can become more likely when are moderately asymmetric.